Comparison of colonial volvocine algae based on phylotranscriptomic analysis of gene family evolution and natural selection. Issue 1 (2nd January 2020) - Hu, Yuxin; Xing, Weiyue; Song, Huiyin; Hu, Zhengyu; Liu, Guoxiang
ABSTRACT: This study is the first to determine the transcriptomes of eight colonial volvocine algae: Pandorina morum, P. colemaniae, Volvulina compacta, Eudorina elegans, E. cylindrica, Yamagishiella unicocca, Colemanosphaera charkowiensis and C. angeleri . By analysing these data together with the whole-genome data of Chlamydomonas reinhardtii and other colonial volvocine algae, we determined 26 979 gene families and 105 single-copy orthogroups. Using the single-copy orthogroups, we adopted a supermatrix and coalescent-based approach to perform phylotranscriptomic analysis of colonial volvocine algae. The phylogenetic relationships of most species were consistent with those of a previous study, and the results showed paraphyly of the genus Pandorina . Then, we analysed gene family expansion and contraction in colonial volvocine algae and found that they exhibited a large number of expanded and contracted gene families. In particular, the common ancestor of the Volvocaceae had the largest number of expanded gene families, which may be associated with the increased volume of extracellular matrix. Finally, using the ML method to analyse the substitution rates among colonial volvocine algae based on single-copy orthogroups, we showed a significantly higher non-synonymous substitution (dN) rate in Tetrabaena socialis . By analysing the differences in the dN/dS ratio, we found that more orthogroups exhibited a significantly higher dN/dS in T. socialis ; we speculate that the higher dN/dS could indicate relaxed selection pressure and that this lower constraint allows the accumulation of more non-synonymous mutations in T. socialis .